The role of said Nursi’s spiritual discourses in contextualizing Islamic moral psychology - Muhsin, Sayyed Mohamed; Karim, Fatimah; Fuad, Iftekhar Jamil (Ankara: Uluslararası Bilimsel Araştırmalar Derneği, 2026)
The Ottoman Empire was deeply rooted in organized traditional spirituality, but the secularization of modern Turkey created significant challenges for traditional scholars and Sufi masters. Living through these turbulent times, Said Nursi chose neither confrontation nor isolation; instead, he pioneered a new form of spirituality grounded in Qur’anic reasoning and practical engagement. This study examines the role of Nursi’s spiritual discourses in contextualizing Islamic moral psychology, focusing on how spirituality shapes individual moral development. By integrating concepts such as divine inspiration, spiritual cognition, and shared practice, Nursi offers a comprehensive framework for moral transformation within the Islamic tradition. Through thematic and comparative analysis of Nursi’s primary works—particularly The Words—this research also evaluates the applicability of his ideas in modern religious counseling. In doing so, it highlights Nursi’s contribution to the broader project of contextualizing Islamic scholarship in response to modernity. Ultimately, the study argues that Nursi presents a holistic and contextually grounded model of Islamic moral psychology, effectively bridging the gap between spiritual tradition and contemporary moral discourse